Coexistence of familial adenomatous polyposis and optic disc drusen in two patients from the same family - Balbaba, Mehmet; Ulaş, Fatih (Gazi Eye Foundation, 2019)
Familial adenomatous polyposis (FAP) is an autosomal dominant disease characterised by the development of multiple adenomatous polyps throughout the colon. There may be other associated systemic abnormalities including extacolonic malignancy. Congenital hypertropy of the retinal pigment epitelium (CHRPE) is a common eye sign in patients with familial adenomatous polyposis. In the current report, we presented two brothers having FAP with optic disc drusen which might be incidental or associated ocular FAP manifestation. © 2019 Gazi Eye Foundation. All rights reserved.
Keywords: Familial adenomatous polyposis; Optic disc drusen